STUDY PERBANDINGAN DINDING PENAHAN TYPE KANTILIVER DENGAN TYPE GRAVITASI PADA PERENCANAAN PENANGANAN LONGSORAN RUAS JALAN SANGA-SANGA – DONDANG STA.4+000 KUTAI KARTANEGARA - AGUSTIAN, IRPAN (KURVA S JURNAL MAHASISWA, 2017)
Indonesia is a disaster prone country such as floods, volcanoes, fires, earthquakes, landslides, etc. One of the factors of this country is prone to disaster is the climate condition. In East Kalimantan, especially in Sanga-Sanga is an area with low landslide susceptibility, but within it there are settlements and some important access roads leading to other areas. It needs special handling for landslide areas such as the construction of retaining walls so that access roads can be passed and activities undertaken by residents in the area can run smoothly.In this final project, comparing two types of Kantiliver type wall and Gravity type, the purpose and objective is to analyze and plan the stability of the archery wall in the construction of retaining wall, which is safe against bolsters, shear and collapse. Analyze the stability of soil bearing capacity and plan its foundation. Analysis method used by Rankine and Coulomb, while the data used before analyzing retaining wall that is primary data consist of Sondir, Boring, and Topography. As for the secondary data in the form of literature study, and references related to the retaining wal.From the analysis of retaining wall using Rankine and Coulomb method for Kantilever type, the result of Rankine Method of stability of style to bolsters is 2,933 ≥ 2 (Safe), shear stability is 2,397 ≥ 2 (Safe), and the stability of collapse is 26,74 ≥ 3 (Safe). While on the Cuolomb method, the stability value of the force against bolsters is 3.252 ≥ 2 (Safe), stability to shear of 2,650 ≥ 2 (Safe), and the collapse stability of 27,951 ≥ 3 (Safe). Gravity type obtained by Rankine method stability value to bolsters equal to 1,760 ≥ 2 (Unsafe), stability to shear of 1,609 ≥ 2 (Unsafe), and the stability of the collapse of 14,366 ≥ 3 (Safe). While in the Cuolomb method, the stability value of the force against bolsters is 1,947 ≥ 2 (Unsafe), the stability to shear is 1,806 ≥ 2 (Unsafe), and the stability of the collapse is 16.185 ≥ 3 (Safe). For pile analysis result of cantilever type obtained by amount of individual pile as many as 30 fruit with 3 row diameter 30 cm, and got P max 170,234 kN <510,221 kN (Aman). As for the type of gravity obtained the number of individual piles of 19 pieces with the number of 2 lines of diameter 30 cm. and obtained value P max 249,505 kN <510,221 kN (Safe).The conclusion of the final project that the authors make is On Kantilever type Rankine and Coulomb method of stability of the style against bolsters, shear, and stability of the whole collapse (Safe). While on Gravity type Rankine or Cuolomb method of force stability to bolsters, and shear (unsafe), only on the stability of the collapse (Safe)